High-school students’ perceptions of the effects of usage course lab in improving ICT literacy - H Rifai; R Juwita; D Yuliana Fitri (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Course Lab, a free e-learning authoring tool created by a Web Soft, offers What You See Is What You Get (WYSIWYG) environment to produce an interactive learning media. Chemistry is the difficult subject for high school students. The students need an Interactive learning media to improve their knowledge. Considering students perception toward interactive learning media is important in successful development ICT literacy student. This study aims to determine students perceptions of using course lab for chemistry subject. Students perceptions are closely related to their achievement. The learning media by the desire of students will make them motivated. This research is qualitative data analysis was done descriptively. The subject of this study were 176 students from 4 schools. The data obtained in this study comes from researchers at the main instrument, the data questionnaire, and interview data is unstructured. The results are students perceptions of using course lab for chemistry subject are in a positive category to improve ICT literacy.